WALT WHITMAN’S USE OF FREE VERSE AND ITS INFLUENCE ON MODERN POETRY (International Journal of Food and Nutritional Sciences, 2023)
This study explores the Walt Whitman’s Use of Free Verse and Its Influence on Modern Poetry. Walt Whitman’s adoption of free verse in his seminal work, Leaves of Grass, represents a pivotal shift in the landscape of American poetry. By rejecting traditional poetic structures—such as fixed meter and rhyme schemes—Whitman introduced a fluid and unstructured form that allowed for a more natural expression of thought and emotion. This innovation enabled him to explore expansive themes like democracy, individuality, and the interconnectedness of all life with a sense of immediacy and intimacy previously unattainable in poetry. Whitman’s free verse is characterized by its irregular line lengths, varied rhythms, and the use of enjambment, which together create a rhythm that mirrors natural speech patterns. This approach not only liberated Whitman from the constraints of conventional verse but also reflected his democratic ethos, celebrating the diversity and unity of human experience.The impact of Whitman’s free verse extends far beyond his own time, profoundly influencing the trajectory of modern poetry. His work laid the groundwork for subsequent poetic experimentation, inspiring major poets such as Ezra Pound, William Carlos Williams, and Allen Ginsberg. These poets embraced and adapted Whitman’s innovations, exploring new forms and techniques that challenged traditional norms and expanded the possibilities of poetic expression. Whitman’s emphasis on freedom and inclusivity has also encouraged poets to address a wide range of themes and subjects, fostering a rich and diverse poetic landscape. His legacy endures as a testament to the power of innovation in poetry and the enduring relevance of his visionary approach to capturing the human experience.